Internet Integration Improves 4C Competencies and Basic Automotive Learning Achievement with SKKNI Standards Through Classroom Action Research - Deni Puji Setiawan; Fuad Abdillah; Budiyanto Budiyanto (Indonesian Journal Publisher, 2026)
Vocational education demands graduates who master technical competencies according to industry standards alongside 21st-century global skills. However, conventional learning that fails to optimize digital literacy often leaves students passive and yields low performance in work safety materials. This study aims to analyze the role of internet integration in improving the 4Cs global competence and SKKNI-based learning achievement of vocational students in Automotive Basic Work. This research employed a Classroom Action Research design conducted across three stages: pre-cycle, cycle I, and cycle II. The subjects comprised 35 class X TKRO students at SMK Ma'arif NU Doro, selected via purposive sampling. Data were collected through performance observations, assessments, and teacher evaluations, then analyzed using percentage techniques against an 85% classical completeness indicator. The results demonstrated a significant increase in average 4C competency from 30% to 90%, while SKKNI learning completeness rose from 20% to 86% by cycle II. Structured internet integration effectively transforms gadgets into productive learning instruments that simultaneously strengthen 21st-century skills and industrial work competency standards. These findings offer a practical pedagogical model for vocational teachers to align digital learning with the demands of graduate job readiness in the modern industrial world.